Formation of the International Trade Community Based on Resource Dependence and Network Theory - Mostafa Heidari Haratemeh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Business communities significantly promote free trade and trade security, so joining the business community is essential for long-term development. Therefore, the research aimed to form an international trade community based on network theory and resource dependence.Methodology: Twenty countries were selected as a sample from the countries that engage in international trade based on the data available from the Comtrade database of the United Nations from 2005 to 2019.Findings: The results showed: 1) the trading partner factor has a positive effect on the formation of international trading communities, that when a country cooperates with a large number of trading partners or has a dominant position in the international trade network, the probability of the country forms the same community with other countries is higher, 2) when a country considers itself dependent on the resources of other countries, the possibility of forming a similar community with other countries increases accordingly and 3) network position plays positive role in regulating the relationship between resource dependence and the international trade community.Originality/Value: Countries that can boost resource trade based on the economic freedom and diversity of the importing country can reduce their dependence on other countries.